Krankheitsbezogener Wissenserwerb durch strukturierte Patienteninformation bei Rheumatoider Arthritis (StruPI-RA): Erste Ergebnisse der StruPI-RA-Studie in Deutschland - Schwarze, M. (Z Rheumatol, 2020)
BACKGROUND/OBJECTIVE: The structured patient information for rheumatoid arthritis (StruPi-RA) program was the first standardized outpatient education program in rheumatoid arthritis (RA) in Germany. The main objective of the study was to determine the efficacy of the StruPi-RA program concerning disease-specific knowledge acquisition in patients with early stage RA or after changing the treatment regimen. METHODS: A total of 61 patients were included in a control group design, 32 in the intervention group (IG) and 29 in the control group (CG). Patients of the IG attended 3 modules of 90 min in a structured patient information program (StruPI-RA) including the topics of diagnostics, treatment and living with RA. Patients in the CG only received information material from the German Rheumatism League. The primary target criterion was the disease-related acquisition of knowledge, measured with the patient knowledge questionnaire (PKQ). Data were collected before and after participation in StruPI-RA. RESULTS: The improvement in knowledge in the IG attending the StruPI-RA compared to the CG was significant in time and group comparisons. No influence of disease duration or educational level was observed. The subscale treatment alone showed a significant difference in the group and time comparison. CONCLUSION: Participation in the StruPI-RA program in early RA was associated with a significant increase in disease-specific knowledge compared to the control group of patients. This leads to better decision-making in terms of treatment, a more beneficial doctor-patient communication and better self-management. In the long term an improvement in treatment adherence and quality of life is expected.